THE INFLUENCE OF AVAILABILITY OF HAMLET POTENTIAL DATA ON DEVELOPMENT IMPLEMENTATION IN LEMPANG VILLAGE, TANETE RIAJA DISTRICT - Muliati; AZ, Wahyul; Fahri, Muhammad (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal